Pengaruh Merk, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Paket Internet Telkomsel (Studi Kasus Mahasiswa FEB Universitas Islam Malang Angkatan 2018) - Muhamad Fatkhur Rizal; Budi Wahono; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study was conducted in order to determine and analyze the influence of brand, price, and product quality on the decision to purchase Telkomsel internet packages. The population in this study were active undergraduate students at the Islamic University of Malang Batch 2018. The approach method used non-probability sampling, namely purposive sampling which is a sampling technique based on certain criteria using a questionnaire distributed to 85 respondents. The analytical method used in this study is multiple linear regression analysis with hypothesis testing using the F test and t test. The results of this study indicate that partially brand, price, and product quality variables have a significant effect on purchasing decisions. While Simultaneously stated that the brand. price, and product quality together influence the decision to purchase Telkomsel internet packages. Keywords: Brand, Price, Product Quality, Purchase Decision